THE INFLUENCE OF ACTIVE KNOWLEDGE SHARING BASED CONTEXSTUAL LEARNING MODELS TOWARD BIOLOGY CRITICAL THINGKING - Sri Dwiastuti, Pradevi Sukma Y, Maridi (P Biologi FKIP UNS Surakarta, 2015)
The purposes of this research are to ascertain the influence of Active Knowledge Sharing Based on Contextual learning strategy toward capability of critical thingking students grade X of SMA Negeri 2 Sukoharjo in academic year 2012/2013.This research is considered as quasi experiment research using quantitative approach. The research was designed using posttest only non-equivalent control group design that applied Active Knowledge Sharing Based on Contextual approach in experimental group and conventional approach with discussion, classical course and question-answer method in control group. The population of this research was all of X degree students at SMA Negeri 2 Sukoharjo in academic year 2012/2013. The sample of this research was established by cluster sampling that choosed X-4 as experiment group and X-7 as control group. The data was collected by using critical thingking test, observation form, and document. The hypotheses analyzed by t-test. The results of this research showed that the mean of student?s capability of critical thinking in experiment class higher than control class, it was 72,97 for experiment class and 64,00 for control class.The result of hypothesis analyzed by t-test, got significant value 0,003 (sig.<0,05), so the Active Knowledge Sharing Based on Contextual learning strategy had very significant effect toward capability of critical thingking. The conclusion of this research showed that application of Active Knowledge Sharing Based on Contextual learning strategy had very significant effect toward capability of critical thingking domain of X grade students at SMA Negeri 2 Sukoharjo in academic year 2012/2013. Key Word :active knowledge sharing based on contextual learning strategy, capability of critical thingking.